Stress Analysis of Bilayer Composite Materials with Various Passion Ratio - Bhuiyan, Yeasin; Salam Akanda, Md. Abdus; Egab, Karim; Raheem Hassan, Hassan; K. Oudah, Saad (International Journal of Engineering and Technology, 2018)
Composites materials are needed because of the widely used in structures and designs. In this work, the stress analysis of two-dimensional bilayer composite materials has a different passion ratio have studied. The materials under consideration are assumed to be perfectly bonded together. Finite difference method is used for the solution of two-dimensional elastic problems. In each layer of the composite, the mechanical properties are isotropic. The results are observed that the results agree well within the acceptable limit, which also confirms the reliability of the finite difference method. Changing in Poissonâ€™s ratio in any layer has significant effects on the results of all layers of the bilayer composite. Due to the mathematical expressions of stresses and displacements for two-dimensional elastic problems, the study of the effects of Poissonâ€™s ratio has a significant influence. Â Â